2022
DOI: 10.5194/egusphere-2022-129
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Water mass transformation variability in the Weddell Sea in Ocean Reanalyses

Abstract: Abstract. This study investigates the variability of water mass transformation (WMT) within the Weddell Gyre (WG). The WG serves as a pivotal site for the meridional overturning circulation (MOC) and ocean ventilation because it is the primary origin of the largest volume of water mass in the global ocean, Antarctic Bottom Water (AABW). Recent mooring data suggest substantial seasonal and interannual variability of AABW properties exiting the WG, and studies have linked the variability to the large-scale clima… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Code and data availability. WMT budgets can be found in the author's GitHub repository (https://github.com/ shanicetbailey/chapter1/tree/v1.0.0, last access: 1 March 2023; https://doi.org/10.5281/zenodo.7776037, Bailey, 2023). The analysis-ready copies of the datasets used for calculating the budgets can be found in the cloud through the Pangeo Catalog (https://catalog.pangeo.io/browse/master/ocean/, Pangeo Catalog, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Code and data availability. WMT budgets can be found in the author's GitHub repository (https://github.com/ shanicetbailey/chapter1/tree/v1.0.0, last access: 1 March 2023; https://doi.org/10.5281/zenodo.7776037, Bailey, 2023). The analysis-ready copies of the datasets used for calculating the budgets can be found in the cloud through the Pangeo Catalog (https://catalog.pangeo.io/browse/master/ocean/, Pangeo Catalog, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Azaneu et al (2014) showed that AABW in the ECCO2 reanalysis is formed by deep convection in the Weddell Sea rather than by on-shelf dense water production and subsequent descent down the continental slope (Menemenlis et al, 2008). A range of data assimilation products (ECMWF-ORAS4 (Balmaseda et al, 2013), CFSR (Saha et al, 2010), MyOcean-UR025.4 (Ferry et al, 2012), ECCO2 (Menemenlis et al, 2008), ECCOV4r4 (Forget et al, 2015), SODA 2.2.4 (Carton and Giese, 2008;Ray, 2011, andSOSE (Mazloff et al, 2010)) are compared in Dotto et al (2014); Aguiar et al (2017), andBailey et al (2023). While some of these reanalyses formed AABW at realistic rates (e.g., ECCOV4r4, SODA, and SOSE), all of the models did not well capture the spatial distribution and variability of AABW compared with observations.…”
Section: Data Assimilation Modelingmentioning
confidence: 99%
“…(They additionally propose a method for decomposing spurious numerical mixing into cabelling and non-cabelling components, but this requires implementing intrusive new diagnostics, so we neglect it here for simplicity). Bailey et al (2023) generalizes the approach from latitude coordinates to a rectangular region with vertical walls. Holmes et al (2021) use a conceptually similar approach to quantify spurious diathermal transports in individual columns, but lose the direct connection to the integrated water mass budgets, such as the boundary-normal transports, as a result.…”
Section: Introductionmentioning
confidence: 99%